2023
DOI: 10.3390/molecules28176291
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Profiling, Characterization and Antimicrobial Efficacy of Silver Nanoparticles Synthesized from Calvatia gigantea and Mycena leaiana Against Multidrug-Resistant Pathogens

Sayab Khan,
Muhammad Fiaz,
Iqbal Ahmad Alvi
et al.

Abstract: The use of natural products isolated from mushrooms against infection, cancer diseases and other oxidative-stress-related diseases is one of the cornerstones of modern medicine. Therefore, we tried to establish a combination of medicinal mushrooms and nanotechnology possibly with the field of medicine for the development of antibacterial agents against these MDR strains. The aim of the research was to understand the molecular identification, characterization and antibacterial action of Calvatia gigantea and My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Other current studies reported the antibacterial efficiency of Ag NPs synthesized using the flavonoid extract of Perilla frutescens, Calvatia gigantea, Mycena leaiana, and Ocimum sanctum. These formulations showed significant inhibition of several pathogens, including Listeria monocytogens, Enterococcus faecalis, A. baumannii, Staphylococcus aureus, P. aeruginosa, K. pneumoniae, Proteus mirabilis, Enterobacter cloacae, and E. coli [21][22][23]. This research underscores the potential utility of Ag NPs in antimicrobial applications, particularly in addressing MDR strains.…”
Section: Introductionmentioning
confidence: 64%
“…Other current studies reported the antibacterial efficiency of Ag NPs synthesized using the flavonoid extract of Perilla frutescens, Calvatia gigantea, Mycena leaiana, and Ocimum sanctum. These formulations showed significant inhibition of several pathogens, including Listeria monocytogens, Enterococcus faecalis, A. baumannii, Staphylococcus aureus, P. aeruginosa, K. pneumoniae, Proteus mirabilis, Enterobacter cloacae, and E. coli [21][22][23]. This research underscores the potential utility of Ag NPs in antimicrobial applications, particularly in addressing MDR strains.…”
Section: Introductionmentioning
confidence: 64%
“…Our research was relate with different previous studies. [1] According to prior research, the most active constituent is water insoluble, therefore more active extracts were dissolved in low polar organic solvents. The highest ZOI of AgNPs was 24 mm against P. aeruginosa and smallest was 10 mm against E. fecalis and A. baumannii.…”
Section: Antibacterial Activity Of Silver Nanoparticlesmentioning
confidence: 99%
“…[33] The observed bands were compared with standard values to identify the functional groups. FTIR spectra showed absorption bands at 2347.36907, 1749.43, and 1263.37, cm 1 indicating the presence of capping agent with the NPs. The band at 1749.43 cm À 1 corresponds to the amide 1 stretching of C=O, bands at 1,263.37 cm À 1 correspond to the symmetrical deformation of amide III and band at 2347.36907 correspond the presence of hydrogen linked to the carbonyl group in the aldehyde (O=C-H) group, and this is a sign of the presence of non-cyclic monosaccharides.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation